Yukio Mishima’s "Confessions of a Mask" (1949): Homosexuality and a Two-Sided Cominig-of-Age Story - Matres García, Ane (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
This article analyzes the role that homosexuality plays in Yukio Mishima’s bildungsroman Confessions of a Mask. To do so, both the paratext and the literary form have been enquired into. In addition, this article focuses on the experiences lived by the main character in order to prove that his sexual orientation generates tension regarding form and content and that this tension results in the questioning of heteronormativity.